Cone Beam Computed Tomographic Measurements of the Descending Palatine Canal and Pteryogomaxillary Region: Implications for Le Fort I Maxillary Osteotomy - Al-Shayyab, Mohammad; Al-Bitar, Zaid; Alsoleihat, Firas; Alzer, Heba; Alshawa, Abedalaziz; Qabba’ah, Khalid; Shaban, Ola; AL-Omiri, Mahmoud K (Jordan Medical Journal, 2025)
Aims: To provide cone-beam computed tomographic (CBCT) measurements of the descending palatine canal (DPC) and pterygomaxillary region, and to demonstrate any possible variations by age, gender and skeletal patterns in a Jordanian population. This may help oral and maxillofacial surgeons (OMFS) in planning and executing a safe Le Fort I maxillary osteotomy. Materials and methods: This radio-anatomical study evaluated CBCT radiographs for patients aged ≥ 18 to 40 years and treated over five years. Distances representing anterior and posterior lengths from the DPC, the narrowest width of pterygoid plates, the depth and diameter of the DPC, and the posterior width of the maxilla were measured by a reliable examiner. Measurements were analyzed according to patients’ age, gender, and skeletal patterns. Student’s t-test and One-Way-ANOVA test were used to analyze data. Results: A total of 93 CBCT radiographs were evaluated and related to a cohort of 93 subjects; 35 (37.6%) males and 58 (62.3%) females, and a mean age (± SD) of 28.98 ± 6.78 years. Almost all measured distances showed significant (P < 0.05) greater values in males than females. Only the posterior width recorded statistically significant (P < 0.05) different distances among the three skeletal pattern groups. All various distances were significantly (P < 0.05) higher in the older age group (30-40 years) than the young age group (18-29 years). Conclusion: CBCT measurements of the pterygomaxillary region, particularly in the young age group and females, with class III skeletal pattern, can provide the safest Lefort I maxillary osteotomy design.